Remuneration Factors in Supporting the Effectiveness of the Performance of the Police of the Republic of Indonesia in the Gorontalo Police - Mohi, Widya Kurniati; Ali, Yuwin; Kadir, Yuyun; Akbar, Muh Firyal; Nahruddin, Zulfan (Faculty of Social and Political Science Universitas Brawijaya, 2020)
This research aims to obtain an overview of the Remuneration Factor in Supporting the Effectiveness of Police Performance Gorontalo Police District Office. The researcher applied qualitative approach while data collection techniques were conducted through interviews to a number of informants, observations and secondary data documentation. By the three indicators of effectiveness of police performance (target achievement, integrity and adaptation) there are some problems encountered. In target achievement indicator, there are some obstacles that obstruct the police performance effectiveness. Whereas the integration indicator showed that the ability of organizations to provide information on Remuneration to members of the National Police has not been effective, as seen from the human resources, there are still those who do not understand about Remuneration and the availability of inadequate infrastructure in the process of conducting socialization. The adaptation indicators showed that the procurement and labor process measurement benchmarks in supporting the performance of Police members have not been effective. It can be seen from the lack of personnel needed in serving the community to support the effectiveness of the police members in Gorontalo Police district office.